(untitled) (Rugby, Great Britain, 2008)
Drawing on twelve case studies and one review conducted in eleven countries in Africa, Asia and Latin America, the contributors show how formal financial institutions and companies use a variety of less formal, often rural, organizations to overcome the information and enforcement problems of serving rural clients. Research indicates that these linkages seem to afford both partners the opportunity to overcome weaknesses experienced when working on their own
Keywords: Microfinance.,Rural development,Tài chính vi mô,Phát triển nông thôn